Catalytic mechanism of DNA backbone cleavage by the restriction enzyme EcoRV: A quantum mechanical/molecular mechanical analysis - Imhof, Petra; Fischer, Stefan; Smith, Jeremy C. (Biochemistry, 2009)
Endonucleases, such as the restriction enzyme EcoRV, cleave the DNA backbone at a specific recognition sequence. We have investigated the catalytic mechanism of backbone phosphodiester hydrolysis by the restriction enzyme EcoRV by means of hybrid quantum mechanical/molecular mechanical calculations. An exhaustive computation of different reaction pathways is performed, thus generating a network of pathways. Comparison of the computed (AM1d/MM) enzymatic reaction pathways with an analogous mechanism for small-molecule model systems [AM1/d and B3LYP/6-31 + + G(d,p)] reveals that the transition barriers for associative hydrolysis, which is more probable in the model systems, are not lowered by the enzyme. Instead, a reaction mechanism which has mostly dissociative character is more likely. The protein environment is tuned to significantly electrostatically stabilize the transition state structures. The direct catalytic impact of essential residues is determined: The magnesium metal ion activates a water molecule, thus facilitating protonation of the leaving group. A reduction of the coordination number of the magnesium metal ion from six to four upon the positioning of the attacking water molecule explains why larger metal ions, such as calcium, are not catalytically active. The nucleophile is generated by the transfer of a proton from the attacking water molecule to a carboxylic oxygen atom of aspartate 90. The catalytic effect of lysine 92 involves proper positioning of the scissile phosphate group and, more importantly, stabilization of the metaphosphate intermediate in an orientation optimal for attack of the nucleophile. ©2009 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18